2020
DOI: 10.1002/tal.1824
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of seismic behavior of the eccentric and conventional diagrid systems

Abstract: SummaryDiagrid system is known for its efficient structural behavior besides its outstanding aesthetic characteristics and architectural flexibility. However, a brief existing study on the nonlinear performance of the diagrid system has reported an inefficient nonlinear behavior. Diagrid with fused‐shear link is a newly introduced system that can solve this flaw in the conventional diagrids and keep the advantages as well. In this paper, this newly introduced system is called eccentric diagrid system (EDS). Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moreover, its eccentric diagrid is one of the latest concrete space structures with improved seismic behavior compared to concentric bracing systems. 29 Flexi-node has the potential to make this type of architecture more adaptive and cost-effective, providing designers with new opportunities to implement their creative visions; however, further research is required in terms of implementing continued curved rebars before the casting process.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, its eccentric diagrid is one of the latest concrete space structures with improved seismic behavior compared to concentric bracing systems. 29 Flexi-node has the potential to make this type of architecture more adaptive and cost-effective, providing designers with new opportunities to implement their creative visions; however, further research is required in terms of implementing continued curved rebars before the casting process.…”
Section: Discussionmentioning
confidence: 99%
“…Each diagonal member is divided into two equal NonlinearBeamColumn elements, and an initial imperfection of 0.5% of the diagonal length is applied at the midpoint, [ 20 ] as shown in Figure 11a. The shear link member is simulated using two DispBeamColumn elements and a ZeroLength element, [ 28 ] as shown in Figure 11b. Based on the method proposed by Koboevic et al, [ 46 ] the shear behavior of the link members is applied to the zero‐length element.…”
Section: Seismic Performance Evaluationmentioning
confidence: 99%
“…In a following paper, Li et al [ 27 ] extended the performance‐based plastic design method to the seismic design of fused diagrid structures. More recently, Dabbaghchian et al [ 28 ] compared the seismic performance of diagrid systems with and without link beam members. The results showed that link members can significantly increase the safety margin of diagrids.…”
Section: Introductionmentioning
confidence: 99%
“…""" |xm@W |=yxR=U |}xRQr |Qw;?=D R}r=v; |Q]k |xm@W |=yxR=U VR}QwQi C}iQ_ w u=UWm |DNU Ow@y@ ? @U |vwt=Q}B [13] "OwW|t |Ov@Qm}B wO =@ Q=DN=Usy |=yxR=U xwQo l} |}xRQr OQmrta 'Q[=L VywSB QO ?=k|xR=U '|rmQw]x@"CU=xOW xU}=kt xOWxDUO |WtN ?=k R}v w|Q]k|xm@W |}=Hx}=H MU=B Q}O=kt 'u}tR |=yCmQL Q@=Q@ QO q=@ |Q}PBh=]av= Crax@ |WtN pQDvm Qw_vt x@ 2020 |QO=kQ}t w jLpy= 'OQwt u}= QO "Ovm|t O=H}= = Q |O=}R |xOvvmpYDt |i=[= |=yu=tr= R= xO=iDU= '|WtN ?=k |=yxR=U QO Ci} QO MU=B u=Wv |oOvvmW |=yQ=Owtv |UQQ@ =@ u=W}= "OvOQm KQ]t = Q Qw=Ht C=k@] QO Q}D wO |SQv= ?PH p}Uv=DB V}=Ri= Ea=@ =yQ}D |xOvvmpYDt |i=[= |=yu=tr= xm OvO=O [14] "OvwW|t |iQYt Oqwi Vy=m w xrRrR = Q |O=}R C}a]k sOa 'xRQru}tR |iO=YD C}y=t =@ |xO}OB '|rm Qw]x@ |= Q@ CWoR=@ |xQwO w u=tR CQwY x@ |v}@V}B "Ovm|t =yxR=U |L=Q] OQ=w xrRrR |UOvyt QO C}a]k sOa u}= "CU= umttQ}e |Qt= '`}=kw u}= O=ONQ "OwW|t h} QaD =yxR=U Q=DiQ R}v w xrRrR |=yOQwmQ |=yx=oO}O R= OQm}wQ wO =@ C}a]k sOa R= Ov=wD|t =yxR=U |}xRQr |Qw;?=D w |Q}PB? }U; |@=} RQ= OQm}wQ |}xRQr |Qw;?=D [15] "Ovm |Q}owrH sw=kt |=yCrmU= |m}t=v}O Q=DiQ QO OwHwt ?…”
mentioning
confidence: 99%